2018
DOI: 10.1093/cvr/cvy252
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of the NLRP3 inflammasome reduces blood pressure, renal damage, and dysfunction in salt-sensitive hypertension

Abstract: AimsRenal inflammation, leading to fibrosis and impaired function is a major contributor to the development of hypertension. The NLRP3 inflammasome mediates inflammation in several chronic diseases by processing the cytokines pro-interleukin (IL)-1β and pro-IL-18. In this study, we investigated whether MCC950, a recently-identified inhibitor of NLRP3 activity, reduces blood pressure (BP), renal inflammation, fibrosis and dysfunction in mice with established hypertension.Methods and resultsC57BL6/J mice were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 46 publications
(83 reference statements)
7
140
0
5
Order By: Relevance
“…Taken together, these findings suggest efficacy of MCC950 in the acute stages following focal TBI in mice; however, it is unknown whether this compound exerts beneficial effects in other species and TBI models (e.g., diffuse TBI). While systemic MCC950 treatment has shown to be well-tolerated in hypertensive mice for as long as 28 days [98], pre-clinical TBI studies have yet to treat with MCC950 for longer than 7 days. Furthermore, the effects of early MCC950 intervention on chronic TBI recovery have not yet been investigated.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
“…Taken together, these findings suggest efficacy of MCC950 in the acute stages following focal TBI in mice; however, it is unknown whether this compound exerts beneficial effects in other species and TBI models (e.g., diffuse TBI). While systemic MCC950 treatment has shown to be well-tolerated in hypertensive mice for as long as 28 days [98], pre-clinical TBI studies have yet to treat with MCC950 for longer than 7 days. Furthermore, the effects of early MCC950 intervention on chronic TBI recovery have not yet been investigated.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
“…The expression of NLRP3 mRNA in renal biopsy specimens of patients with hypertensive or vascular nephrosclerosis is higher than that in normal kidneys, suggesting that NLRP3 plays a role in hypertension-related kidney disease [57]. Krishnan et al indicated that activation of the NLRP3 inflammasome in the kidney is associated with salt-sensitive hypertension [58,59]. Interestingly, in a hypertensive mouse model induced by angiotensin II, NLRP3 deficiency showed a protective effect on blood pressure, while the deletion of ASC did not [60].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Additionally, systemic deletion of NLRP3 in mice remarkably ameliorate proteinuria and podocyte damage [63]. In a hypertensive mouse model, MCC950, an NLRP3 inhibitor, can significantly reduce blood pressure and fibrosis, alleviate kidney inflammation, and protect against renal dysfunction [59]. Current studies have shown that the investigation of inflammasome-independent functions is of great significance to discover the pathogenesis of hypertension [64].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…One day prior to N. brasiliensis infection, mice were treated with either PBS vehicle or 10 mg/kg MCC950 (Sigma) by intraperitoneal injection in a 100 µl volume, a dose which has been previously shown to inhibit inflammasome activity (43). Injections were repeated daily up until the experimental endpoint.…”
Section: Nlrp3 Inhibitionmentioning
confidence: 99%